Formation of primary school students’ communicative language learning strategies - Baltabayeva, A.K.; Kagazbayev, Zh.A.; Eskazinova, Zh.A.; Mustagaliyeva, G.S. ("Акад. Е.А. Бөкетов ат. Қарағанды ун-ті" КЕАҚ баспасы, 2022)
The changes taking place in modern society require modification in the educational space and a different setting of educational goals that take into account the state, social, personal needs and interests of pupils. Learning at school becomes a process of interaction of learners with a teacher and classmates. The pupil becomes an active participant in the educational process and, in cooperation with the teacher or other learners solve real-life situations. At the primary stage of instruction it is necessary to lay the foundations of communication, since this age is favorable for building communicative competence. The modern dynamically developing information society defines forming and developing pupils' communicative skills as one of the important tasks of teaching and learning. The article reveals the essence of the concept of "Communicative Language Learning Strategies" of junior schoolchildren, focuses on their influence on the pupil’s self-development leading to the planned result of foreign language education according to the state overall standard of primary education of the Republic of Kazakhstan.
Бастауыш сынып оқушыларының коммуникативті əмбебап оқу əрекеттерін қалыптастыру
Формирование коммуникативных универсальных учебных действий младших школьников
Keywords: communicative language learning strategies; self-development; communication; real-life situations; communicative competence; foreign language education; primary school